Diseño de una herramienta digital para la selección de una bomba centrífuga en operaciones costa afuera con los requerimientos de la norma API 610/ISO13709 (2022)
The absence of oil innovation has been one of the main problems evidenced in some countries affecting its marketing and distribution, one of the main reasons being the lack of investment in new technologies such as offshore, preventing this, the exploration of new fields; That is why the initiative has been taken to develop a digital tool for the selection of a centrifugal pump in offshore operations, which will allow its easy selection, optimizing the calculation time, and will provide the client with an optimal time for the selection of the pump. pump, this tool is focused on the benefit of the community, since it will be free, it is only required to enter data that must be taken from well control, such as viscosities, flow rates, cross-sectional areas, among others, and thus, the tool It will provide the suction and discharge pressures accompanied by their respective graphs for the selection of the centrifugal pump.